Efficacy of electrical stimulation for treatment of migraine - Jiang, Chao (Medicine (Baltimore), 2019)
BACKGROUND: The objective of this study is to assess the efficacy of electrical stimulation (ES) for the treatment of patients with migraine. METHODS: MEDLINE, EMBASE, Cochrane Library, CINAHL, PsycINFO, Scopus, Web of Science, Allied and Complementary Medicine Database, ProQuest Nursing and Allied Health, Chinese Biomedical Literature Database, and China National Knowledge Infrastructure will be searched for eligible studies. All electronic databases will be searched from inception to the present with no language restriction. Two authors will independently carry out study selection, data collection, and study quality assessment, respectively. RevMan 5. 3 software will be used for statistical analysis. RESULTS: This study will summarize high quality evidence on the efficacy and safety of ES for the treatment of migraine. CONCLUSION: This study will establish the accurate results of ES for migraine to facilitate the clinical practice and guideline development. PROSPERO REGISTRATION NUMBER: PROSPERO CRD42019147480.